Pengaruh Penerapan E-Filing, Sanksi Perpajakan, Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di Kota Bandar Lampung - Zya Pasha Melando; Irawan Irawan; Eksa Ridwansyah (Politeknik Negeri Lampung, 2022)
Taxes are the main source of government & development financing. Realizing the magnitude of the tax benefits, the government implements various ways in order to maximize tax revenue through increasing taxpayer compliance by carrying out tax reforms, namely improving tax regulations and administration systems. Data obtained from the regional office of the Directorate General of Taxes in Bengkulu and Lampung shows the low compliance of individual taxpayers in the city of Bandar Lampung.This study aims to determine the effect of the application of e-filing, tax sanctions, and knowledge of taxation on individual taxpayer compliance in Bandar Lampung City. The data used are primary data obtained through the distribution of questionnaires. The sample used in this study was 100 respondents who met the sample criteria from the total population of individual taxpayers registered at the Primary Tax Service Office in Bandar Lampung City. The method of analysis in this study is multiple linear regression analysis. The results of this study indicate that (1) the application of e-filing has a positive and significant effect on individual taxpayer compliance in Bandar Lampung City. (2) Tax sanctions have no significant effect on individual taxpayer compliance in Bandar Lampung City. (3) Knowledge of taxation has a positive and significant effect on individual taxpayer compliance in Bandar Lampung City.